Implementasi Sistem Informasi Berbasis Web (Studi Kasus Gereja GKE Sion Palangkaraya) - Nugroho, Bayu Pratama; Jayanti, Sherly (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2017)
With its growing congregation of a church, then the church service requires an advance and improve the better. Therefore, a website for the church is important in providing a solution to the constraints that happen. News GKE SION neighborhood church congregation had previously only made in paper media obtained during worship Sunday only, so that the risk of damage / loss of information occur frequently. Overcoming the limitations of community news, then made the information systems that are faster and can be accessed easily without the constraints of time to build web-based applications. This website uses technologies that AJAX and Web 2.0 Content Management System (CMS) on the admin menu and menu content. This website generates message of the church in the form of online media format to get various information bulletin church and worship services that include Profile, Regarding GKE Church congregation SION along News is updated every week. With this website the churches helped in getting the information the church.